Identifying the target genes of SUPPRESSOR OF GAMMA RESPONSE 1, a master transcription factor controlling DNA damage response in Arabidopsis. (24th March 2018) - Ogita, Nobuo; Okushima, Yoko; Tokizawa, Mutsutomo; Yamamoto, Yoshiharu Y.; Tanaka, Maho; Seki, Motoaki; Makita, Yuko; Matsui, Minami; Okamoto‐Yoshiyama, Kaoru; Sakamoto, Tomoaki; Kurata, Tetsuya; Hiruma, Kei; et al.
Summary: In mammalian cells, the transcription factor p53 plays a crucial role in transmitting DNA damage signals to maintain genome integrity. However, in plants, orthologous genes for p53 and checkpoint proteins are absent. Instead, the plant‐specific transcription factor SUPPRESSOR OF GAMMA RESPONSE 1 (SOG1) controls most of the genes induced by gamma irradiation and promotes DNA repair, cell cycle arrest, and stem cell death. To date, the genes directly controlled by SOG1 remain largely unknown, limiting the understanding of DNA damage signaling in plants. Here, we conducted a microarray analysis and chromatin immunoprecipitation (ChIP)‐sequencing, and identified 146 Arabidopsis genes as direct targets of SOG1. By using ChIP‐sequencing data, we extracted the palindromic motif [CTT(N)7 AAG] as a consensus SOG1‐binding sequence, which mediates target gene induction in response to DNA damage. Furthermore, DNA damage‐triggered phosphorylation of SOG1 is required for efficient binding to the SOG1‐binding sequence. Comparison between SOG1 and p53 target genes showed that both transcription factors control genes responsible for cell cycle regulation, such as CDK inhibitors, and DNA repair, whereas SOG1 preferentially targets genes involved in homologous recombination. We also found that defense‐related genes were enriched in the SOG1 target genes. Consistent with this finding, SOG1 is required for resistance against the hemi‐biotrophic fungus Colletotrichum higginsianum, suggesting that SOG1 has a unique function in controlling the immune response. Significance Statement: In this manuscript, we revealed the target genes of SOG1, a master transcription factor controlling DNA damage response in Arabidopsis . By comparing the target genes between SOG1 and p53, we found that SOG1 has a unique function in controlling homologous recombination and immune responses.